ASP.NET Core Security - Wenz, Christian (Manning Publications, 2022)
ASP.NET Core Security teaches you the skills and countermeasures you need to keep your ASP.NET Core apps secure from the most common web application attacks. With this collection of practical techniques, you will be able to anticipate risks and introduce practices like testing as regular security checkups. You’ll be fascinated as the author explores real-world security breaches, including rogue Firefox extensions and Adobe password thefts. The examples present universal security best practices with a sharp focus on the unique needs of ASP.NET Core applications.